(untitled) (Research, Society and Development, 2021)
Pressure injuries (LPP) are the result of prolonged pressure on the skin, mediated by little movement, requiring the implementation of preventive and therapeutic actions to the subjects. The aim of this study is to present the main evidence and clinical recommendations in nutritional care for patients with pressure injuries. It is a Systematic Review, in LILACS, SciELO, MEDLINE and ScienceDirect databases, based on the following descriptors: Nutrition, Nutritionist, Pressure Injury and Nutritional Status, in which the Boolean operators “AND” and “OR”, Making the different combinations in the databases. The corpus of this investigation comprised 15 scientific articles, including a supplement and two books, published in the last five years. In this way, in order to present scientific evidence around the LPP in an organized way, three tables were prepared containing the selection of the articles, the main nutritional recommendations in the management of the LPP and the main nutrients recommended to assist in the healing process. It was identified that the nutritional status is a decisive factor for recovery and progress for the lesions, with nutritional screening tools indicated for early detection to implement the therapeutic action plan. Therefore, it is concluded that the integration of the interdisciplinary team in the prevention and treatment of PPL means enhancing the production of comprehensive health care and, at the same time, equitable, by valuing the subject in its complexity and human uniqueness with a focus on quality of life, longevity and patient safety.